TEATER TUTUR KUNOUNG TUPAI JANJANG MENJADI SPIRIT TEATER MODERN - Meria Eliza (LPPMPP Institut Seni Indonesia Padangpanjang, 2011)
explore the value – the value of tradition and preserve the noble values of the nation merepukan a form of love of culture and treasures of the nation one of the efforts made, namely to let the tradition (art) is still alive according to its time and place it in proper place with the values and traditions do not remove itself and let the art was developed in order to stay alive and there for example art Kunoung Tupai Janjang in the middle of the social life of society Kerinci-Jambi. Initially kunoung Tupai Janjang is just a folk tale that is told (in his tale), which is also called the theater said, due to the modernization of society, the habit of storytelling is shifted even abandoned. To maintain the tradition of spoken (storytelling) of which is to innovate new ways to transform the theater said this in the form of one-man play performed by brahim.then make the theater said Kunoung Tupai Janjang as spirit to the development of modern theater. thus the theater said as one of the traditional arts will continue to live and develop in accordance with its time.